2000 IEEE Nuclear Science Symposium. Conference Record (Cat. No.00CH37149)
DOI: 10.1109/nssmic.2000.949220
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of static and dynamic cardiac perfusion thallium-201 SPECT

Abstract: Clinically, cardiac SPECT is performed with static imaging protocols and visually assessed for perfusion defects based upon the relative intensity of myocardial regions. Dynamic imaging, however, has the potential to provide quantitative measures of flow, possibly improving diagnosis. The objective of this study was to compare the information content of dynamic and static thallium SPECT imaging as measures of myocardial perfusion. To make this comparison, canine studies were performed each with an occlusion pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…See [1] and the references given there for related canine studies. We assume a myocardium slice with two dynamic zones showing different time profiles.…”
Section: Simulated Heart Studymentioning
confidence: 99%
See 1 more Smart Citation
“…See [1] and the references given there for related canine studies. We assume a myocardium slice with two dynamic zones showing different time profiles.…”
Section: Simulated Heart Studymentioning
confidence: 99%
“…Dynamic functional imaging with SPECT camera systems has been recognized as a promising new option for medical diagnostics, and several approaches to visualizing and quantifying dynamic parameters of time-varying processes in the body have recently been proposed (see [1,2,3,4,5,6]). Dynamic Single Photon Emission Computed Tomography (dSPECT) is one such modality, whose most important aspect is its ability to reconstruct time-varying activity distributions from dynamic data acquired on a standard protocol with a single rotation of the camera system (cf.…”
Section: Introductionmentioning
confidence: 99%
“…However, early feasibility studies using conventional photo-multiplierbased SPECT systems [7][8][9] and recently a new generation of SPECT cameras using solid-state photon detectors 10 showed potential to expand quantification of absolute blood flow and flow reserve also into the single-photon domain.…”
mentioning
confidence: 99%
“…The wash-in rate parameters were used to reflect flow. The flow data from the microspheres were obtained by well counting the tissue samples and visually registering the photographs of the myocardial slices with the summed static short-axis data for use as a gold standard [4]. The patient data were analyzed by comparing the wash-in rate parameters from the cluster analysis and the semi-automatic method to the summed intensities obtained from the summed static data.…”
Section: Canine and Patient Studiesmentioning
confidence: 99%
“…INTRODUCTION W ORK done by several investigators has shown the potential of dynamic cardiac SPECT to provide quantitative measures of myocardial physiological parameters [1]- [4]. Our group has shown that the use of tracers such as 99m Tc-labelled teboroxime (teboroxime) and Tl) with dynamic cardiac SPECT yields parameters that correlate with myocardial blood flow in addition to providing improved defect contrast [2]- [4].…”
mentioning
confidence: 99%